PENCEGAHAN COVID 19 DI DESA TANJUNGJAYA KECAMATAN BANGUNREJO KABUPATEN LAMPUNG TENGAH PROVINSI LAMPUNG - Wakib Kurniawan; Widada Hamid; Samsul Huda (Institut Agama Islam Tribakti Kediri, 2022)
Real Work Lecture (KKN) is a form of community service activity that is special, because in KKN, education and teaching, research and community service are integrated into it and involve a number of students and a number of teaching staff plus elements of the community. KKN is an intracurricular lecturing activity in the form of community service carried out by students in an interdisciplinary and cross-sectoral manner. This activity is aimed at developing the sense of sensitivity and social cognition of students as well as assisting the development process. The PAR (Participatory Action Research) based devotional model was chosen as the team service method. Where PAR has three key variables, namely, Participatory, Action (action) and Research (research). Zainuddin et al (2014:104) state, the three variables are formulated as follows: (1) Research, this stage is the stage of research on the problems faced by the community, the problem is understood in such depth and detail, so that the problem can clearly know the causes and consequences, (2) Action (action), after knowing these problems in depth and detail, then enter the second step, namely the search for alternative solutions to solve the problem, which is then translated into several work program items. which will be implemented, and (3) Participatory, the two items above are carried out in a participatory manner, meaning by involving all components of society in identifying problems and solving techniques together. There are several results of work programs carried out by students in preventing the spread of the Covid-19 pandemic which spread in the village of Tanjungjaya, Bangunrejo District, Central Lmapung Regency, Lampung Province, including the following: 5M Education Program for Covid-19 Prevention, 5M Education Program and Distribution of PPE (Masks) and Environmental Cleanliness Service Program.